Japan's Cultural Diplomacy Towards the Arab World: Building Bridges and Strengthening Relations - Habib Badawi (Universitas Pancasakti Tegal, 2024)
This scholarly investigation delves into the nuanced realm of Japan's cultural diplomacy endeavors directed at the Arab world. The central focus of this study lies in a meticulous analysis of the multifaceted strategies and initiatives employed by Japan to cultivate closer relations and facilitate heightened mutual comprehension. The scholarly exploration unfolds through a comprehensive examination of Japan's dynamic cultural engagement with Arab nations. This pursuit entails a judicious dissection of the historical, political, and economic determinants that have indelibly molded this bilateral relationship. The contours of this examination encompass in-depth scrutiny of governmental policies, meticulously crafted exchange programs, and culturally immersive showcases. The overarching intent of these endeavors is to gauge the resonating impact of Japan's cultural diplomacy efforts. This resonance manifests itself through the cultivation of sanguine perceptions, the fortification of bilateral affiliations, and the facilitation of a constructive discourse channel between Japan and the Arab world. By adopting a discerning approach, replete with an analysis of pertinent case studies and the discerning insights of domain experts, this study identifies a spectrum of challenges and opportunities intrinsic to Japan's cultural diplomacy regarding the Arab world. Such challenges and opportunities are unearthed to foster a nuanced understanding of this diplomatic enterprise. In closing, this scholarly endeavor proffers insightful recommendations aimed at the judicious advancement of Japan's cultural diplomacy endeavors in the Arab world. These recommendations are derived from a profound synthesis of the distilled insights generated through this academic scrutiny.